Optimization of the Synthesis of Flavone-Amino Acid and Flavone-Dipeptide Hybrids via Buchwald-Hartwig Reaction - Pajtás, Dávid; Kónya, Krisztina; Kiss-Szikszai, Attila; Džubák, Petr; Pethő, Zoltán; Varga, Zoltán; Panyi, György; Patonay, Tamás (The Journal of organic chemistry, 2017)
The article describes the development of Buchwald-Hartwig amination of different bromoflavones with amino acid and peptide derivatives as nitrogen source giving unique structures. The previously observed racemization, which occurred during the synthesis of flavone-amino acid hybrids, was successfully prevented in most cases. The biological assays of these novel structures showed cytotoxic effects on different cancer cell lines.
Keywords: screeningové testy protinádorových léčiv; Amino Acids; spektrální analýza; Flavones; kinetika; aminokyseliny; Humans; lidé; dipeptidy; mikrobiální testy citlivosti; Drug Screening Assays, Antitumor; Kinetics; Cell Line, Tumor; Microbial Sensitivity Tests; Spectrum Analysis; Dipeptides; nádorové buněčné linie; flavony